2007
DOI: 10.1210/jc.2007-0619
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Early Atherosclerosis in Obese Children and Adolescents

Abstract: Adiponectin more than conventional CV risk factors and inflammation status may be related to early atherosclerosis in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
130
5
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(176 citation statements)
references
References 38 publications
21
130
5
18
Order By: Relevance
“…Similarly FBS was also higher in the overweight/obese group although no subject fulfilled criteria for diagnosis of diabetes. Similar observations have been made in different studies in children and indicate the presence of risk factors for metabolic syndrome in obese children [19,22].…”
Section: Correlation Between Hscrp and Other Parameterssupporting
confidence: 89%
“…Similarly FBS was also higher in the overweight/obese group although no subject fulfilled criteria for diagnosis of diabetes. Similar observations have been made in different studies in children and indicate the presence of risk factors for metabolic syndrome in obese children [19,22].…”
Section: Correlation Between Hscrp and Other Parameterssupporting
confidence: 89%
“…Another finding of great value in this investigation was a negative correlation between change in HOMA-IR and changes in adiponectin concentration. Beauloye et al 6 showed a negative correlation between adiponectin and carotid IMT in children and adolescents, but only at baseline conditions. These results reinforce the importance of adopting strategies that promote an improvement of HOMA-IR and adiponectinemia, which could influence IMT measurements.…”
Section: Discussionmentioning
confidence: 97%
“…Adiponectin may be more closely related to atherosclerosis in obese children than are conventional cardiovascular risk factors and inflammation status. 6 For example, it has been demonstrated that high adiponectin concentration can suppress the development of atherosclerosis in susceptible mice. 32 Consistent with this hypothesis, our study verified a negative correlation between change in HOMA-IR and change in adiponectin concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations